Magnetic Barkhausen emission in lightly deformed AISI 1070 steel - Capó Sánchez, J.; de Campos, M.F.; Padovese, L.R. (Journal of magnetism and magnetic materials, 2012)
The Magnetic Barkhausen Noise (MBN) technique can evaluate both micro- and macro-residual stresses, and provides indication about the relevance of contribution of these different stress components. MBN measurements were performed in AISI 1070 steel sheet samples, where different strains were applied. The Barkhausen emission is also analyzed when two different sheets, deformed and non-deformed, are evaluated together. This study is useful to understand the effect of a deformed region near the surface on MBN. The low permeability of the deformed region affects MBN, and if the deformed region is below the surface the magnetic Barkhausen signal increases. ► Evaluated residual stresses by the magnetic Barkhausen technique. ► Indication about the relevance of micro-and macro-stress components. ► Magnetic Barkhausen measurements were carried out in AISI 1070 steel sheet samples. ► Two different sheets, deformed and non-deformed, are evaluated together. ► Magnetic Barkhausen signal increases when deformed region is below the surface.